FROM PITYRIASIS LICHENOIDES CHRONICA TO SYPHILIS AND HIV – A DETECTIVE’S APPROACH - Lorena Dolački; Josip Prnjak; Liborija Lugović-Mihić (Liječnički vjesnik, 2023)
Pityriasis lichenoides chronica (PLC) is a rare, non-infective dermatosis of unknown etiology characterized by reddish-brown papules with potential overlying mica-like scales, which sometimes progress to cutaneous T-cell lymphoma. Lesions mimicking PLC can (rarely) occur as a presentation of anunderlying infectious disease or as a paraneoplastic syndrome